Effect of impeller design on drop sizes and mass transfer in immiscible liquid-liquid system in a stirred vessel / Reza Afshar Ghotli - Reza Afshar , Ghotli (2018)
Impeller design is one of the determinant factors for mixing performance in stirred vessels. In this work, performances of conventional and new impeller designs were evaluated for liquid-liquid dispersion. Drops size analysis and mass transfer characteristics studies were conducted at a specific energy input. The experiments were conducted in a standard cylindrical tank of 0.3 m diameter with a single impeller set-up. The impellers used were Rushton turbine, up-flow and down-flow pitched-blade turbines, half-circular blade turbine, elliptical blade turbine, parabolic blade turbine, hydrofoil impeller and double circular blades turbine that covers both the axial and radial flow impellers. Prior to mass transfer characteristics study and drop size analyses, the power number, mixing time and air entrainment speed were determined at various Reynolds numbers for all the impellers in a single phase system. Mixtures of palm-oil in water in a range of 1-10% v/v were selected as a liquid-liquid system. The power was measured using a suspended motor system and photographic method was used for drop size measurements. Mass transfer study was performed in a system with a hydrolysis reaction. The results showed that at the same energy dissipation rate, the hydrofoil impeller produced the largest mean drop size diameter (d32) and the double curved blade turbine produced the smallest, about 37% lower. In the case of radial flow impellers, smaller drops size values were obtained for the impellers with larger curvature angle. Increasing the dispersed phase from 1 to 10% increased the d32 by about 20 to 40% due to higher collision frequency between drops. Therefore, higher interfacial areas were obtained using double curved blade impeller and pitched blade down flow turbine. Mass transfer coefficients were determined using Batchelor proposed correlation. The highest mass transfer coefficients were obtained at 1.08×10-5 and 1.02×10-5 (m.s-1) for the double curved blade impeller and pitched blade down flow turbine, respectively. This proved the suitability of these impellers for liquid-liquid dispersion within the Reynolds number range of 50×104 to 80×104. In the case of reactive system, the experiments at the same energy dissipation rate (ɛ=0.16 m2/s3) recorded the highest production rate in a range of 0.21 ×10-3 to 0.55×10-3 and 0.20 × 10-3 to 0.54 × 10-3 mole/m3 for double curved blade and pitched blade down flow impellers, respectively. This is due to the larger impeller swept area and longer residence time of vortices at the impeller tip speed which resulted in a higher mass transfer rate within the tank. In conclusion, for an energy efficient system, the pitched blade down flow turbine is the appropriate selection for the liquid-liquid systems whereas at the same energy consumption, the double curved blade impeller could be a suitable choice because of the better performance even in higher dispersed phase volume fraction.